The Effect of Variation-Based Shadow Badminton Training on Improving the Footwork Ability of Sports Education Students - Zalindro, Ade; Fadlan, Abdur Rohim; Pra adha, Ozha Wahyu (Jurnal Patriot, 2026)
Problem : The low footwork skills of students are inextricably linked to the training methods employed in the learning process. Footwork training in badminton lectures has generally been conducted conventionally, involving monotonous repetition of basic movements, lacking variety, and providing minimal movement stimuli that mimic real-life playing conditions. Purpose : This study aims to determine the effect of variation-based shadow badminton training on improving the footwork abilities of Sports Education students.. Methods : The study used an experimental method with a pretest–posttest control group design. The study sample consisted of 90 students, divided into two groups: the experimental group (n = 45) and the control group (n = 45). The experimental group was given treatment in the form of variation-based shadow badminton training, while the control group was given conventional training. The research instrument used a nationally and internationally validated badminton footwork ability test. Data analysis was performed using normality tests, homogeneity tests, and independent sample t-tests with a significance level of 0.05. Resuluts : The results of the study showed that there was a significant increase in footwork ability in both groups (p < 0.05), but the increase in the experimental group was significantly higher than the control group (p = 0.000). Conclusion : These findings indicate that variation-based shadow badminton training significantly improves students' footwork skills. Therefore, variation-based shadow badminton training is recommended as an effective training method to improve the quality of badminton learning in higher education.